Enhancing Biodiesel Yield from Castor Seed Oil through Co-Solvent-Assisted Transesterification Using n-Hexane - Yasyifa, Annisa; Atin, Ro; Istiani, Alit; Anggorowati, Heni (Eksergi, 2025)
The growing demand for sustainable energy sources has increased interest in biodiesel as a renewable alternative to petroleum-based fuels. This study explored the effect of reaction time, molar ratio of methanol to oil, and catalyst concentration with the addition of co-solvent on the transesterification of castor seed oil, aiming to increase methyl ester yield. n-Hexane was chosen as the co-solvent due to its physical compatibility with methanol, thus facilitating reactant solubility and product separation. Using response surface methodology (RSM) with Minitab software, process parameters such as co-solvent ratio, reaction duration, and temperature were optimized. The optimized conditions (1:5 co-solvent ratio, 55°C, 20 min) resulted in a biodiesel yield of 98.86%, with GC-MS confirming a methyl ester content of 99.79%. The resulting biodiesel yield met the requirements of the Indonesian National Standard (SNI) as well as viscosity but had a heating value that was slightly below the standard range. These findings highlight the effectiveness of co-solvent integration in improving biodiesel production from vegetable oil feedstocks.